Meningkatkan Daya Dukung Tanah dengan Pondasi Mini Pile Pada Gedung PT. Maju Jaya Kecamatan Ngasem, Kab Kediri - Enggar Triatma Pamungkas; Edy Gardjito; Sigit Winarto; Faiz Muhammad Azhari (Jurnal Manajemen Teknologi & Teknik Sipil, 2021)
Foundation is a lower structure that serves to withstand the load of the upper structure. One type of foundation inside is mini pile foundation. Mini pile foundation is widely used in construction with light to heavy loads. This study aims to plan the foundation of mini pile with carrying capacity and dimensions of the stake that is safe for the PT building's lower structure. MAJU JAYA, which will be used as an office. Based on the data of sondir test results obtained from the field on the building project's construction, the stake's foundation will be planned using the mayerhoff method. This plan obtained the results of axial load (sigma Vertical Ultimate) Ʃvu of 145.56, the carrying capacity of a single pole of 31.17 tons, and the group's carrying capacity pole of 173.84 tons. This result will be planned the foundation of mini pile with dimensions of 20x20 with a depth of 8 meters a number of 8 poles.